2001
DOI: 10.1007/s004210100498
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prolonged continuous exercise on hormone responses to subsequent exercise in humans

Abstract: This study examined the possibility that fatigue may modify the hormone responses to exercise. A group of 12 endurance trained athletes ran for 2 h (blood lactate concentrations of approximately 2 mmol x l(-1)) in order to induce fatigue. The subjects exercised for 10 min at 70% maximal oxygen uptake before (1st test) and after (2nd test) the 2 h run to assess hormone responsiveness. A 1 min anaerobic power test was performed to assess muscle power. Cortisol, growth hormone, testosterone and insulin concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 20 publications
(39 reference statements)
3
39
1
3
Order By: Relevance
“…The fact that we found reduced cortisol levels in particular can give rise to questions but has already been mentioned after prolonged intense exercise and is still being debated. In a previous study, Viru et al [29] suggested that fatigue from prolonged endurance activity may introduce a resetting in the pituitary-adrenocortical component of the endocrine system, expressed by either intensified or suppressed endocrine functions. These authors have examined in men the cortisol response to a standardized test of shortterm submaximal exercise (10 min cycling ergometry at 70% maximal oxygen uptake) performed before and after 2 h prolonged exercise, and at the same time they have assessed muscle performance through a 1-min anaerobic power test at the end of the 10-min cycling.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that we found reduced cortisol levels in particular can give rise to questions but has already been mentioned after prolonged intense exercise and is still being debated. In a previous study, Viru et al [29] suggested that fatigue from prolonged endurance activity may introduce a resetting in the pituitary-adrenocortical component of the endocrine system, expressed by either intensified or suppressed endocrine functions. These authors have examined in men the cortisol response to a standardized test of shortterm submaximal exercise (10 min cycling ergometry at 70% maximal oxygen uptake) performed before and after 2 h prolonged exercise, and at the same time they have assessed muscle performance through a 1-min anaerobic power test at the end of the 10-min cycling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the criteria of Viru et al (2001) were then used to categorize subject groups by percent hormone change into (+) responders (increases), (-) responders (decreases), or non-responders (no change). Responders required a hormone concentration change exceeding the assay bio-variability and the human biological intra-individual variability for fT3, the physiologically most active thyroid hormone (see Viru et al 2001). Descriptive statistics were calculated for all variables [mean (SEM)].…”
Section: Statisticsmentioning
confidence: 99%
“…7 The internal load, or the relative physiological strain resulting from the external training factors, is also crucial to determining both the stress imposed and subsequent adaptation to training. 9 A combination of both the external and internal load is therefore important for training since the uncoupling or divergence of external and internal loads may differentiate between a nonfatigued and a fatigued athlete. 3,7 This approach is particularly relevant in "closed loop" sports like cycling where the performance outcome is time, and the power produced by the rider is known to have a relatively precise association with the performance time.…”
Section: Methods For Monitoring Fatiguementioning
confidence: 99%